Determinación de helicobacter pylori y su relación con los factores de riesgo para desarrollar gastritis en los policías municipales - Pacheco Castro, María Fernanda (2015)
The colonization by the Helicobacter pylori is the most common and chronic bacterial infection in humans. It’s a problem of public health due to 60% of worldwide population suffer it, being the population from developing countries who are most likely to acquire it due to the predisposing risks and factors to which they are exposed (1). The gastritis is etiologically and multifactorial, taking note that in only one patient may involve multiple factors to develop it the most common one is the Helicobacter pylori infection (2). In this investigation as an objective it was planted to determinate the Helicobacter pylori, and be aware of the risk factors to which they are exposed in order to develop gastritis in municipal police officers and the relationship with the positive results from the H. pylori with predisposing risk factors to develop gastritis in the population studied. A descriptive study was held with a transversal cut in which 62 men and 38 women participated belonging to the Municipal Urban Security Unit of the city of Loja who were quantitatively determined the presence of blood serum antibodies lgM anti Helicobacter pylori by ELISA, we could observe that 65% presented positive results for the infection by the H. pylori. Also a survey was applied to the participants of the study to know which are the risk factors that they are exposed to in order to develop gastritis it was determine that this is caused by: unsuitable feeding schedules, stress due to their work schedule, eating food in the street and also spicy ones, greasy or spicy, smoking and drinking alcohol. Regarding to the relationship in the positive cases of Helicobacter pylori with the risk factors we could determinate the total of 65 positive cases occupy an 100%, eating at an unsuitable time, just like stress 100%, eating food in the street spicy or greasy 92%, smoking 69.2% and drinking about 60%. Key words: Helicobacter pylori, ELISA.